Oligocene marine Date Mussel from Plaznica brook near Poljšica, West Slovenia - Mikuž, Vasja (Geologija, 2006)
In paper the bivalve of species Lithophaga ornatissima (Mayer-Eymar, 1886) is described, found in a corallite in Oligocene beds of the Plaznica creek at Poljšica near Podnart. This is the first find of this litophaga species in Slovenia. In literature no finds of fossil date mussels are mentioned from surroundings of Poljšica in Upper Carniola.